(3eUHGM GdOjGLi hcga GddGLi hZhK GdQGLis - (3GHf Yjf GdaVdGA , eMeO Hf YHO Gddg GdfGSN, eLO GdOjf CHh GdeYGdjs ((3CMeO Hf CHj GdbGSe GdeZQHi GdHQgGfi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bgQ GdLHGHQI dGSjeG SaM GdebWe GdPi JTQa HCMjGFgG hdeG cGf ehdGfG GdhRjQ jQZH ai RjGQJgG CLHJ Cf CLeY dg gPG GdLeY GdeajO s
(3BNQgG (B:s
(3ef GYJQa HaVdge hLeY TedfG Hge hehdGfG GdeUGMH GdhRjQ GdPi TgOJ CQHGH GdeedcI HaVdg , hLeY gPG GdcJGH ef CLdg ehdGfG GdUGMH JGL GdOjf s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B180 s
Keywords: (3GdJGQjNs